Aquiles e Odisseu no Hípias Menor de Platão, (ou, A disposição moral do homem verdadeiro) - Eduardo Lucas Alves Rodrigues (2023)
The objective of this dissertation is to enter the study of the Lesser Hippias dialogue, specifically aiming to clarify how the notions of ἀληθής (true) and of ψευδής (false, liar) and are developed through the contrast of the images between Achilles and Odysseus. The Lesser Hippias is a short Socratic dialogue in which Plato presents us, from the characterization of Achilles and Odysseus, a dialogue between Socrates and the sophist Hippias around the theme of truth (ἀλήθεια) and lie (ψεῦδος), which ends up unfolding it is an important discussion about voluntary and involuntary action, as well as the relationship between knowledge and the good (HUNTER, 2016, p.1). In this research, in the first part, presents an overview of the known characterizations of Achilles and Odysseus present in the Greek from the archaic period, until the beginning of the classic, all indicating the possible information available in Plato's time about the two heroes, Mythical information they are known for centuries of cultural transmission, orality, ancient arts or rare written works. By opposing the Socratic and Sophist illustrations of Achilles and Odysseus, sometimes presented as true men, sometimes as false or versatile, we intend to present a possible reading key for the Lesser Hippias, demonstrating Plato's criticisms of the difficulty of the traditional culture of his time in establish the criteria to understand the notion of virtue and, mainly, to understand what, in fact, the true man would be to the fullest (ἀληθέστατος).